Цій людині в житті поталанило (до 95-річчя Г. С. Пшеничного) - Ємельянова, Т. (Архіви України, 2009)
The article is dedicated to Gordey Pshenichny – the well known Ukrainian archivist, one of the founders and the long-term leader of the Central State Film, Photo and Sound Archive of Ukraine.